Bio‐Graphene Sensors for Monitoring Moisture Levels in Wood and Ambient Environment. Issue 4 (21st February 2023) - Mulla, Mohammad Yusuf; Isacsson, Patrik; Dobryden, Illia; Beni, Valerio; Östmark, Emma; Håkansson, Karl; Edberg, Jesper
Abstract: Wood is an inherently hygroscopic material which tends to absorb moisture from its surrounding. Moisture in wood is a determining factor for the quality of wood being employed in construction, since it causes weakening, deformation, rotting, and ultimately leading to failure of the structures resulting in costs to the economy, the environment, and to the safety of residents. Therefore, monitoring moisture in wood during the construction phase and after construction is vital for the future of smart and sustainable buildings. Employing bio‐based materials for the construction of electronics is one way to mitigate the environmental impact of such electronics. Herein, a bio‐graphene sensor for monitoring the moisture inside and around wooden surfaces is fabricated using laser‐induced graphitization of a lignin‐based ink precursor. The bio‐graphene sensors are used to measure humidity in the range of 10% up to 90% at 25 °C. Using laser induced graphitization, conductor resistivity of 18.6 Ω sq −1 is obtained for spruce wood and 57.1 Ω sq −1 for pine wood. The sensitivity of sensors fabricated on spruce and pine wood is 2.6 and 0.74 MΩ per % RH. Surface morphology and degree of graphitization are investigated using scanning electron microscopy, Raman spectroscopy, and thermogravimetric analysis methods. Abstract : A humidity and moisture sensor are produced directly on wood using a bio‐based ink in combination with laser‐induced graphitization. Highly sensitive sensors are achieved which can be used to monitor the moisture content inside of the wood, as well as the surrounding air. The devices are demonstrated in controlled environment using wireless readout electronics.